GE_GERICHTE P/17501/2020 vom 2. Mai 2024 - GE Cour de justice (2024)
BLANCHIMENT D'ARGENT;VIOLATION DES RÈGLES DE LA CIRCULATION;PRINCIPE DE L'ACCUSATION;ADMINISTRATION DES PREUVES | CP.305bis; LCR.90.al2; CPP.9; CPP.148